Comparative study of effectiveness of augmentation with ECT in clozapine resistant schizophrenia (CRS) and non-clozapine resistant schizophrenia (Non-CRS). (2nd August 2021) - Grover, Sandeep; Shouan, Anish; Chakrabarti, Subho; Sahoo, Swapnajeet; Mehra, Aseem
Abstract: Background: There is limited evidence for different treatment strategies in patients with clozapine resistant schizophrenia (CRS). Aim: To determine the effectiveness of ECT in patients with clozapine resistant schizophrenia and compare the same with a group of patients with non-clozapine resistant schizophrenia, receiving ECT. Results: Out of a total of 68 patients with schizophrenia, 27 (38.66%) of patients had CRS. With 6 ECTs, there was a significant reduction in PANSS positive, negative, general psychopathology, prosocial score and depression symptoms in the CRS ( p  < 0.001) and Non-CRS group ( p  < 0.001), but no statistically significant difference was seen between the 2 groups in terms of proportion of patients showing >40% response on PANSS total score. The reduction in PANSS score of >40% in CRS group was seen in 48.1% of patients in the positive symptoms subscale, in 25.9% of patients in negative symptoms subscale, in 46.7% of cases in the general psychopathology subscale, in 44.4% of the patients in Depression subscale, in 29.6% of the patients in the modified prosocialsubscaleand in 29.6% of the patients in total PANSS score. Conclusion: ECT is an effective augmentation strategy for patients with CRS and it is as effective as when used in patients with non-CRS.